2021
DOI: 10.1242/jcs.258462
|View full text |Cite
|
Sign up to set email alerts
|

The Bardet–Biedl syndrome complex component BBS1 controls T cell polarity during immune synapse assembly

Abstract: Components of the intraflagellar transport (IFT) system that regulates the assembly of the primary cilium are co-opted by the non-ciliated T cell to orchestrate polarized endosome recycling and to sustain signaling during immune synapse formation. Here we have investigated the potential role of BBS1, an essential core component of the Bardet-Biedl syndrome complex that cooperates with the IFT system in ciliary protein trafficking, in the assembly of the T cell synapse. We demonstrate that BBS1 allows for centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 81 publications
2
22
0
Order By: Relevance
“…Consistent with this evidence, we observed that the centrosomal 19S RP pool increases early during IS formation, to progressively return to baseline with IS maturation (23). Additionally, we found that the centrosome failed to polarize to the IS in T cells pretreated with proteasome inhibitors and that the mislocation of the centrosome in these cells is paralleled by F-actin accumulation at the centrosome, supporting a role for the centrosomal proteasome in IS formation.…”
Section: The Ubiquitin-proteasome System (Ups) and Bbs1 Cooperate In ...supporting
confidence: 86%
See 4 more Smart Citations
“…Consistent with this evidence, we observed that the centrosomal 19S RP pool increases early during IS formation, to progressively return to baseline with IS maturation (23). Additionally, we found that the centrosome failed to polarize to the IS in T cells pretreated with proteasome inhibitors and that the mislocation of the centrosome in these cells is paralleled by F-actin accumulation at the centrosome, supporting a role for the centrosomal proteasome in IS formation.…”
Section: The Ubiquitin-proteasome System (Ups) and Bbs1 Cooperate In ...supporting
confidence: 86%
“…In recent years new, unexpected players have been identified in the mechanisms that regulate centrosomal F-actin clearance and centrosome polarization during IS assembly. We and Ibañez-Vega et al have implicated the ubiquitin-proteasome system (UPS) in this process (23,58,59) (Figure 1). The UPS is a major degradation pathway in eukaryotic cells and is responsible for proteolysis of cytosolic proteins regulating a variety of cellular processes.…”
Section: The Ubiquitin-proteasome System (Ups) and Bbs1 Cooperate In ...mentioning
confidence: 89%
See 3 more Smart Citations